2021
DOI: 10.31234/osf.io/ytdsj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the effectiveness of a universal eHealth school-based prevention program for depression and anxiety, and the moderating role of friendship network characteristics

Abstract: Background. Lifetime trajectories of mental ill health are often established during adolescence. Effective interventions to prevent the emergence of mental health problems are needed. In the current study we assessed the efficacy of the CBT informed Climate Schools universal eHealth preventive mental health program, relative to a control. We also explored whether the intervention had differential effects on students with varying degrees of social connectedness. Method. We evaluated the efficacy of the Climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…These effects might equate to a relaKvely small number of young people deterioraKng in one trial, parKcularly if the effect is only found in a subgroup of parKcipants 16 , but the same effect size can be very impachul when intervenKons are scaled up to reach large proporKons of young people, as is the goal with universal school intervenKons 11,23 . For example, if delivered to all the 3.6m students at state-funded secondary schools in the UK 24 , an intervenKon with a negaKve effect size of d=0.1 (comparable to that found in a recent study 12 ) could lead to 62,765 addiKonal young people scoring above threshold for high levels of internalising problems (see Box 1 for simulated data).…”
Section: Recommendaon 1: Acknowledge the Possibility Of Potenal Harmmentioning
confidence: 71%
See 3 more Smart Citations
“…These effects might equate to a relaKvely small number of young people deterioraKng in one trial, parKcularly if the effect is only found in a subgroup of parKcipants 16 , but the same effect size can be very impachul when intervenKons are scaled up to reach large proporKons of young people, as is the goal with universal school intervenKons 11,23 . For example, if delivered to all the 3.6m students at state-funded secondary schools in the UK 24 , an intervenKon with a negaKve effect size of d=0.1 (comparable to that found in a recent study 12 ) could lead to 62,765 addiKonal young people scoring above threshold for high levels of internalising problems (see Box 1 for simulated data).…”
Section: Recommendaon 1: Acknowledge the Possibility Of Potenal Harmmentioning
confidence: 71%
“…In addiKon, we recommend that researchers familiarise themselves with qualitaKve research that has asked young people for detailed insights into their experience of school-based mental health intervenKons 11,20,32 . Based on the exisKng literature, we recommend that depressive symptoms, anxiety and prosocial behaviour are always included as outcomes that can show potenKally harmful effects [12][13][14][15][16] .…”
Section: Recommendaon 2: Idenfy Types Of Potenal Harmmentioning
confidence: 99%
See 2 more Smart Citations
“…We define potential harm as any negative outcomes/outcome or adverse event that could plausibly be linked to the school intervention itself . For example, one universal CBT-based intervention was found to increase internalising symptoms in the intervention group, but not in the control group, at six and 12 months post intervention (Andrews et al, 2021). Other studies have found negative outcomes for specific subgroups.…”
Section: Introductionmentioning
confidence: 97%